Implikatur Percakapan dalam Lelucon dan Anekdot Papua (Kajian Pragmatik) - Supriyanto Widodo (Balai Bahasa Provinsi Papua, 2019)
Wisecrack and anecdote as part of folklore will linger in society because have function in that society. Folklore's form like anecdote or mop and wisecrack are still make a abode lush at Papuan because really functioning. There are many person considered that wisecrack and anecdote (mop) are one of black humor form. According to expert, black humor can function as attenuator for unsatisfactory, abomination, and confusion. Pragmatic, one of linguistics branch, is study about meaning in its relationship with situation says. With pragmatic through study of saying implicate that available in wisecrack and anecdote (mop) Papuan gets to be known that is still a lot of Papuan society that its science about things which concern its knock about life less is equal too, e.g. concerns health, education, the right and obligation as citizen, etc.